Desenvolvimento e caracterização de nanopartículas lipídicas sólidas modificadas com ácido hialurônico para administração oral de insulina - Custódio, Gabrielle Racoski (2018)
The oral administration of insulin stands out as the most convenient, simple and compatible way for patients, since it provides comfort and it can control the glucose homeostasis. This study produced and evaluated a polymer-lipid nanotransporter for the oral delivery of insulin by double emulsion and solvent emulsification/evaporation using ethyl palmitate and hyaluronic acid (HA) of 13 and 55 kDa. The nanoparticles showed an average diameter of 300 nm, negative surface charge, encapsulation efficiency of 35% and they were thermally stable when analyzed by differential scanning calorimetry. The in vitro release with simulated gastrointestinal fluids demonstrated the protection ability to encapsulated insulin. The nanoparticles have shown to be safe at potential therapeutic concentrations, since they did not cause cytotoxicity to intestinal epithelial cells. Finally, the permeability of nanoencapsulated insulin through Caco-2 monolayers and Caco-2/HT29-MTX model correlated with the slow release rates and did not show differences between them. These results indicated that the molar weight of HA did not show differences in both the characterization and the therapeutic response of the prepared nanoparticles, which could be considered as a good carrier for the oral administration of insulin.